2021
DOI: 10.1007/s40368-021-00649-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, experience and perception regarding molar incisor hypomineralisation (MIH) among dentists and dental hygienists in Oslo, Norway

Abstract: Aim The aim of this study is to gather baseline information on knowledge, perceptions, clinical experience and treatment options regarding MIH among dental care providers in Oslo, Norway, before a larger epidemiological study. Methods An electronic questionnaire was distributed to dentists (n = 88) and dental hygienists (n = 47) working in the Public Dental Service (PDS) in Oslo. The questionnaire consisted of five sections related to sociodemographic, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
(98 reference statements)
9
19
1
Order By: Relevance
“…PDs showed higher probability for reporting achievement of adequate anaesthesia and problems due to hypersensitivity. These results are not in agreement with findings from most of the studies [7,18,22] that mainly report child's behaviour as the main barrier to care. Multiple dental visits, regular follow-ups and extensive dental interventions increase dental anxiety and have a negative influence on the children's behaviour.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…PDs showed higher probability for reporting achievement of adequate anaesthesia and problems due to hypersensitivity. These results are not in agreement with findings from most of the studies [7,18,22] that mainly report child's behaviour as the main barrier to care. Multiple dental visits, regular follow-ups and extensive dental interventions increase dental anxiety and have a negative influence on the children's behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…Up to date, there is limited evidence, from questionnaire-based surveys in Europe, Asia and Australia [3][4][5][6][7][8][9][10][11][12] regarding knowledge and attitudes of dentists about MIH. All studies reported that it is a widespread clinical problem, whose diagnosis and management is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In the present questionnaire, most respondents reported that genetic factors had a significant role in the etiology of MIH [ 18 ], with different views among GDPs and PDs. Similar results were reported in Saudi Arabia, Egypt, and Norway [ 19 21 ]. PDs have encountered more MIH-affected children during their practice and perceived that MIH prevalence is increasing in Syria.…”
Section: Discussionsupporting
confidence: 89%
“…The present study reveals that most of the dental practitioner respondents agree that genetic, environmental factors, acute medical conditions affecting mother or child, chronic medical conditions affecting mother and child, and antibiotic use and other medications are associated with the aetiology of MIH. The same responses were also reported in the latest studies [ 31 , 32 ]. Regarding fluoride exposure, PDs have better knowledge that fluoride exposure is not related to MIH.…”
Section: Discussionsupporting
confidence: 87%
“…Data were collected for four weeks in November–December 2021. A modified questionnaire based on earlier publications was used [ 27 , 28 , 29 , 30 , 31 , 32 ]. Data on socio demography, knowledge, and confidence in diagnosing and treating MIH, preference for continuing education, and opinion about the MIH clinical training necessity were obtained.…”
Section: Methodsmentioning
confidence: 99%